Chinese investment in Taiwan: challenge or opportunity for Taiwan’s high-technology industrial development? - Lee, Chun-yi; Yin, Ming-xi (German Institute of Global and Area Studies, 2017)
Cross-Strait economic activities are no longer one-directional. The Taiwanese government opened the doors to Chinese investment in 2009. The aim of this paper is to address the crucial question: What are the impacts of Chinese investment on Taiwan’s high-technology industrial development? Two further questions immediately follow: Will Chinese investment put Taiwanese industrial development at risk? Will an influx of Chinese investment provide a turning point for Taiwanese industry?